2017
DOI: 10.1021/acs.est.7b02857
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate Aerosols Promote Lung Cancer Metastasis by Epigenetically Regulating the Epithelial-to-Mesenchymal Transition (EMT)

Abstract: Secondary inorganic aerosols (SIA), particularly sulfate aerosols, are central particulate matter (PM) constituents of severe haze formation in China and exert profound impacts on human health; however, our understanding of the mechanisms by which sulfate aerosols cause malignancy in lung carcinogenesis remains incomplete. Here, we show that exposure to secondary inorganic aerosols induced the invasion and migration of lung epithelial cells, and that (NH)SO exerted the most serious effects in vitro and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
(99 reference statements)
0
13
0
2
Order By: Relevance
“…EMT is a process that increases the metastasis and invasive potential of tumor cells, with losing epithelial cell characteristics and acquiring a mesenchymal pheno-type, including decreasing epithelial markers (cytokeratin or E-cadherin) and up-regulating mesenchymal indicators (VIM or N-cadherin) or transcription factors (Twist, Snail) [ 35 37 ]. Usually, inhibiting E-cadherin can induce invasiveness-related N-cadherin expression [ 38 , 39 ]. VIM may enhance migration and invasiveness and related to reduce E-cadherin and upregulating N-cadherin, while increased VIM is correlated with poor prognosis [ 20 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a process that increases the metastasis and invasive potential of tumor cells, with losing epithelial cell characteristics and acquiring a mesenchymal pheno-type, including decreasing epithelial markers (cytokeratin or E-cadherin) and up-regulating mesenchymal indicators (VIM or N-cadherin) or transcription factors (Twist, Snail) [ 35 37 ]. Usually, inhibiting E-cadherin can induce invasiveness-related N-cadherin expression [ 38 , 39 ]. VIM may enhance migration and invasiveness and related to reduce E-cadherin and upregulating N-cadherin, while increased VIM is correlated with poor prognosis [ 20 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…FN1, a member of the glycoprotein family, is involved in cell migration and adhesion [30]. Many studies have reported that FN1 has an indispensable role in EMT [31][32][33][34]. FN1, together with E-cad and VIM, serves as a marker for EMT in non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, в воздухе происходит формирование вторичных частиц в результате химических реакций c газообразными загрязняющими веществами, которые, в свою очередь, являются продуктом происходящей в атмосфере трансформации окислов азота и серы либо выбрасываются автотранспортом и промышленностью. Вторичные частицы в основном содержатся в мелкодисперсных РМ [12,13].…”
Section: Reviewsunclassified